Effect of fractional graphite alloying on the properties of aloe-vera mediated green-synthesized NiOx-C composite - A. K. Mahmud Hasan; D. K. Sarkar; M. S. Basar; Munira Sultana; Mohammad Junaebur Rashid; Mohammod Aminuzzaman; Md. Shahiduzzaman; Hamad F. Alharbi; Md. Akhtaruzzaman (Journal of Taibah University for Science)
This study emphasizes the synthesis of nickel oxide (NiOx + C) nanoparticles with varied graphite (C) proportions (1%, 2.5%, 5%, 7.5%, and 10%) using Aloe-Vera natural extract as a green reducing agent. Prepared NiOx + C nanostructures exhibited consistent X-ray diffraction patterns with no additional C peak, signifying enhanced interlayer spacing. The crystalline size (Dp) decreased from 27 nm to 20 nm with an increase in the amount of carbon (C). The determined bandgap (Eg) was 2 eV higher than bulk material due to formation extra energy level at defect sites. The shoulder peak at 1620 cm−1 agrees with the disorder-induced band from C and second-order bands of C at about 2700 cm−1 for NiOx + C. FESEM images confirm the hexagonal morphology. Not much particle aggregation was observed except for 10% C content. The selected area electron diffraction (SAED) confirms the existence of NiOx crystalline orientations including planes (111), (200), (220), (311), and (222).